Analysis of Problem Based Learning Model in Increasing Interest in Learning Indonesian Language in Grade IV Elementary School Students - Noviana, Ilva Ira; Ifrianti, Syofnidah; Asiah, Nur (TERAMPIL: Jurnal Pendidikan dan Pembelajaran Dasar, 2025)
The purpose of this study was to analyze the application of the Problem Based Learning (PBL) Model in increasing interest in learning Indonesian language in grade IV Elementary School students. The research method used is quantitative using bibliometric analysis with data taken from various articles and journals related to PBL from 2015 to 2025. Data collection used Publish or Perish (PoP) media and data visualization using VOSviewer. The initial number of articles taken was 1000 articles and then narrowed down to 100 articles for analysis. Data analysis consists of five steps, namely the search stage in the Google Scholar database using Publish or Perish or (PoP) software; selection of keywords used which are obtained are stored in RIS (Research Information System) format; refinement of search results/filtering stage; compilation of initial statistical data; data analysis stage. The results of the study obtained the year of publication with the highest number in 2024 with a percentage of 36%, while the institution or institution with the largest number of articles was Sanjaya Tamansiswa University. The publisher with the largest number of articles is Jurnal Educatio FKIP Unima. The article publication with the highest number of citations was written by Irma Septiani and Albertus Djoko Lesmono with the title "Analysis of Student Learning Interest Using Problem Based Learning Model with STEM Approach on Vector Material in Class X MIPA 3 SMAN 2 Jember" which was published in 2020 and published by Jurnal Pembelajaran Fisika, where the number of citations was 132. It can be concluded that there has been an increase in publications on PBL and its relevance in the context of language education. Recommendations for further research include further exploration of the impact of PBL in various educational contexts and subjects.